(untitled) (Bangladesh Journal of Neurosurgery, 2026)
Aims:To determine the demographic, clinical, radiological, and surgical factors associated with the outcomes in study participants with traumatic acute extradural hematoma who were surgically managed in the Neurosurgery Department at a tertiary-level hospital in Bangladesh. Materials and Methods: This interventional study included 81 study participants of any age and sex with traumatic acute EDH who were surgically managed at the Department of Neurosurgery of Chittagong Medical College Hospital from September 2022 to February 2024. EDH was diagnosed by computed tomography (CT) scan of the head, and the surgical technique was craniotomy and evacuation of haematoma. Data regarding the demographic, clinical, radiological and surgical factors of these study participants were recorded and examined in relation to outcome at three months by Glasgow Outcome Scale (GOS). Good outcome was defined by GOS score 4 or 5 and poor outcome was defined by GOS score 1-3. Results: The median age of the study participants were 22 (range: 1.5-60.0) years. There was a male preponderance (87.7%) with a male-female ratio of 7.1:1. The most common mode of injury was road traffic accident (55.5%). Out of 81 study participants, 56.6% with good outcome had preoperative GCS of 9–13, and all 5 study participants with poor outcome had preoperative GCS between 3–8 (P<0.05). All study participants with poor outcome had unilateral mydriasis (p<0.05). The most frequent site of haematoma was the temporoparietal region (27.1%). All five study participants with poor outcome had haematoma volume >50ml (p<0.05). The mean midline shift (6.9 ± 0.4 mm) was higher in study participants with poor outcome than the study participants with good outcome (p<0.05). Basal cistern obliteration was found to have a significant association with poor surgical outcome (p<0.05). Out of 81 study participants 93.8% had good outcome and poor outcome or mortality rate was 6.2% at 3 months post-surgery. Conclusions: Majority of the study participants with traumatic acute EDH had good surgical outcome. Only five study participants had shown poor surgical outcomes with a preoperatively low GCS (<9), unilateral mydriasis, higher hematoma volume (>50ml), significant mid line shift, and basal cistern obliteration. Keywords: , , Bang. J Neurosurgery 2024; 14(1): 38-45